The Usage Of An Audio-Linguistic Method Of Learning English As A Foreign Language By Intermediate Students - Vohidjon Qizi, Fazilatkhon Ikromova; Qarshiyeva Shakhnoza Valiyevna (The American Journal of Social Science and Education Innovations, 2021)
This article describes the aspects of audio- lingual method of language learning. As a conclusion, the main advantages of the method, in the case of its application as an integral part of the methodology of teaching English as a foreign language, and disadvantages that may occur in the case of its autonomous or remote use. Thus, we can say that the audio-lingual method will be a weighty addition to the general methodology of teaching English as a foreign language.